Implementation of Islamic Religious Education Learning Management Based on Intellectual, Emotional, and Spiritual Quotients at Institut Agama Islam Ma’arif NU Metro Lampung - Muhammad Yusuf (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The article was to reveal the concept and the implementation Islamic Religious Education (PAI) learning management, the perception of the PAI Study Program lecturers, and the obstacle and solutions of implementation of IESQ-based PAI learning management at Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung. This research was a field research at the IAIMNU PAI Study Program. The sources of data are the leaders, lecturers and the documents such as vision, mission, goals, curriculum. Collecting data used observation guide sheets, interview guidelines, and documentation. The result showed that the implementation of IESQ-based PAI learning management includes (a) planning namely the preparation of objectives, teaching materials, syllabus and SAP, preparation of supporting devices, determining learning evaluation methods and systems, dominant IQ (61.1%); (b) organization which refers to the curriculum, managing classes, and interactive communication in the classroom, dominant on IQ (68.3%); (c) leadership namely apperception, motivation, active learning strategy, communicative, humor, discipline, formal dress, developing self-confidence, togetherness, group dynamics, managing class, and dominant on IQ (96.3%); (d) evaluation, namely partial evaluation of the process and results, process technique, namely assessing attitude, activity, product, and accountability, result technique, namely UTS and UAS, and dominant on IQ (60%). Keywords: Learning Management, Spiritual Quotients, IESQ Learning Management